High-Performance Al–Si Coatings Toward Enhancing Oxidation Resistance of Tungsten by Halide-Activated Pack Cementation - Zhu, Liu; Zhang, Yu-Xiang; Wang, Jin-Fang; Luo, Lai-Ma (Frontiers in Materials, 2020)
Abstract